2015
DOI: 10.1002/cctc.201500482
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Biomass Gasification to Syngas Over Highly Dispersed Lanthanum‐Doped Nickel on SBA‐15

Abstract: Catalytic biomass gasification is an environmentally benign solution to energy problems. A series of Ni catalysts on mesoporous SBA‐15 are synthesized with various La2O3 loadings. The catalytic activity of unpromoted Ni/SBA‐15 catalyst indicates that it has a high carbon formation rate, resulting in fast deactivation. In contrast, addition of La2O3 to Ni/SBA‐15 catalyst helps to remove deposited carbon by formation of oxycarbonate, resulting in higher CO production. A 1 % La doping in the Ni/SBA‐15 catalyst is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 105 publications
0
11
0
Order By: Relevance
“…After H 2 reduction at 800 °C for 1 h, there are no more peaks for NiO (Figure ). Instead, typical Ni peaks are observed, which indicates the reduction from NiO to Ni . The crystal size of Ni is calculated to be approximately 4 nm.…”
Section: Resultsmentioning
confidence: 95%
“…After H 2 reduction at 800 °C for 1 h, there are no more peaks for NiO (Figure ). Instead, typical Ni peaks are observed, which indicates the reduction from NiO to Ni . The crystal size of Ni is calculated to be approximately 4 nm.…”
Section: Resultsmentioning
confidence: 95%
“…28,29 The H 2 -TPR was performed on the sample (100 mg) up to 600°C and held for 1 hour, followed by cooling down to room temperature under He gas. The pulse amount of N 2 O gas was then injected to the system to oxidize the surface metallic site of the reduced catalyst until saturation.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Previous studies have shown that SiC as a catalyst support has many advantages under high temperature or strongly exothermic non‐oxidation reactions, e. g. CO 2 hydrogenation . In addition, La 2 O 3 has been regarded as an effective additive to improve the dispersion of active species and thus increased the activity and stability of the catalysts …”
Section: Introductionmentioning
confidence: 99%